Validation and Quantification of Theophylline and Salbutamol using Ion Pair Liquid Chromatography - Shanti Laksmi Sophi; Sudibyo Martono; Abdul Rohman (Indonesian Journal of Pharmacy, 2016)
Salbutamol and theophylline are administered in combination orally to provide the sinergistic effect of drugs. The aim of this study is to develop and to validate ion pair liquid chromatography to determine both drugs in pharmaceutical dosage form, especialy in syrup dosage form. Separation of drugs was performed with Spherisorb C-18 column (250 x 4.6 mm; 10 um). The mobile phase used is the mixture of acetic acid 1% : methanol (60 : 40 v/v) which contain 3.5 mM sodium-1-octanesulphonate, as ion pairing reagent. The mobile phase was delivered isocratically with flow rate of 1 mL/min. UV detection was set at wavelength of 277 nm. The developed method was validated in terms of linearity, precision, accuracy, selectivity, and sensitivity. The precision of the method was evaluated using repeatability assay having relative standard deviation (RSD) values of 0.41–0.70 % for theophylline and 0.08 – 0.24 % for salbutamol. The recovery percentages are in the range of 98.28–101.02% (theophylline) and 100.71–101.60% for salbutamol. The developed method meets the validation requirement for analysis of salbutamol and theophylline simultaneously in syrup dosage form. Furthermore, the method also provides acceptable result for syrup and tablet dosage forms containing Salbutamol and theophylline only, and tablet containing the combination of Salbutamol and theophylline.Keywords: teophyllin, salbutamol, HPLC, sodium-1-octanesulphonate, validation.